Molecular basis of alpha 1-antitrypsin deficiency and emphysema associated with the alpha 1-antitrypsin Mmineral springs allele. - Curiel, D T (1990)
The Mmineral springs alpha 1-antitrypsin (alpha 1AT) allele, causing alpha 1AT deficiency and emphysema, is unique among the alpha 1AT-deficiency alleles in that it was observed in a black family, whereas most mutations causing alpha 1AT deficiency are confined to Caucasian populations of European descent. Immobilized pH gradient analysis of serum demonstrated that alpha 1AT Mmineral springs migrated cathodal to the normal M2 allele. Evaluation of Mmineral springs alpha 1AT as an inhibitor of neutrophil elastase, its natural substrate, demonstrated markedly lower than normal function. Characterization of the alpha 1AT Mmineral springs gene demonstrated that it differed from the common normal M1(Ala213) allele by a single-base substitution causing the amino acid substitution Gly-67 (GGG)----Glu-67 (GAG). Capitalizing on the fact that this mutation creates a polymorphism for the restriction endonuclease AvaII, family analysis demonstrated that the Mmineral springs alpha 1AT allele was transmitted in an autosomal-codominant fashion. Evaluation of genomic DNA showed that the index case was homozygous for the alpha 1AT Mmineral springs allele. Cytoplasmic blot analysis of blood monocytes of the Mmineral springs homozygote demonstrated levels of alpha 1AT mRNA transcripts comparable to those in cells of a normal M1 (Val213) homozygote control. Evaluation of in vitro translation of Mmineral springs alpha 1AT mRNA transcripts demonstrated a normal capacity to direct the translation of alpha 1AT. Evaluation of secretion of alpha 1AT by the blood monocytes by pulse-chase labeling with [35S]methionine, however, demonstrated less secretion by the Mmineral springs cells than normal cells. To characterize the posttranslational events causing the alpha 1AT-secretory defect associated with the alpha 1AT Mmineral springs gene, retroviral gene transfer was used to establish polyclonal populations of murine fibroblasts containing either a normal human M1 alpha 1AT cDNA or an Mmineral springs alpha 1AT cDNA and expressing comparable levels of human alpha 1AT mRNA transcripts. Pulse-chase labeling of these cells with [35S]methionine demonstrated less secretion of human alpha 1AT from the Mmineral springs cells than from the M1 cells, and evaluation of cell lysates also demonstrated lower amounts of intracellular human alpha 1AT in the Mmineral springs cells than in the normal M1 control cells. Thus, the Gly-67 --> Glu mutation that characterizes Mmineral springs causes reduced alpha 1AT secretion on the basis of aberrant posttranslational alpha 1AT biosynthesis by a mechanism distinct from that associated with the alpha 1AT Z allele, whereby intracellular aggregation of the mutant protein is etiologic of the alpha 1AT-secretory defect. Furthermore, for the alpha 1AT protein that does reach the circulation, this mutation markedly affects the ability of the molecule to inhibit neutrophil elastase; i.e., the alpha 1AT Mmineral springs allele predisposes to emphysema on the basis of serum apha 1AT deficiency coupled with alpha AT dysfunction.